HAEMOPARASITIC INFECTIONS AND ASSOCIATED RISK FACTORS AMONG CATTLE SLAUGHTERED AT KATSINA CENTRAL ABATTOIR, KATSINA STATE, NIGERIA - Muhammad, Usman Zulkifilu; Auta, Timothy; Atalabi, Ebenezer Tolulope (FUDMA JOURNAL OF SCIENCES, 2023)
Cattle are essential for the growth and maintenance of a country’s economy, but different blood parasites (Haemoparasites) can reduce their production, which causes both direct and indirect financial losses for the livestock industry. The incidence of hemoparasites and risk factors related to them were investigated in cattle butchered at the principal abattoir in Katsina. At the point of slaughter, 500 blood samples were aseptically taken, processed, and checked for hemoparasites by identifying parasites on thin blood smears stained with Giemsa. A prevalence of 8.4% was recorded overall. Anaplasma, Babesia, Microfilaria, and Trypanosoma, four genera of bovine hemoparasites, had prevalence rates of 4.0%, 2.4%, 2.4%, and 0.8%, respectively. The prevalence of hemoparasites was found to be greater in females (8.8%) than in males (7.7%), however there was no statistically significant difference (P 0.05). All breeds evaluated during the study tested positive for haemoparasites; the highest frequency, 16.1%, was found in Adamawa Gudali, followed by Sokoto Gudali (10.3%), White Fulani (7.2), and Red Bororo (6.8%). According to the study’s findings, there is no statistically significant difference between breeds in the prevalence of haemoparasites (P 0.05). Young people were more likely to have high prevalence (9.1%) than adults (6.4%) or those who were older (8.7%). The current study has identified the haemoparasite status of cattle put to death at the principal abattoir in Katsina. Consequently, to increase livestock productivity, appropriate preventive and control measures are required.